2010
DOI: 10.2174/1875042701002020055
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in L-Arginine Metabolism After Lung Transplantation~!2009-11-12~!2010-03-25~!2010-05-04~!

Abstract: Since the discovery of nitric oxide (NO) in biological systems more than 20 years ago, it became widely accepted that endogenous NO plays a key role in the regulation of a variety of physiological processes. NO is involved in reperfusion injury and chronic rejection after solid organ transplantation. Arginase is an enzyme that competes with NO synthases for the common substrate L-arginine. Increased arginase activity alters L-arginine metabolism and reduces substrate availability for NO synthases, and thereby … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 100 publications
1
2
0
Order By: Relevance
“…Previous studies had reported low NO production after lung transplantation in humans [11,40]. Studies on the effects of preservation and lung transplantation on NO in animal models revealed similar results.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Previous studies had reported low NO production after lung transplantation in humans [11,40]. Studies on the effects of preservation and lung transplantation on NO in animal models revealed similar results.…”
Section: Discussionsupporting
confidence: 63%
“…Previous studies have suggested that alterations in the l-arginine/NO metabolism may contribute to complications after lung transplantation [11]. For instance, NO released by macrophages and neutrophils may contribute to the pathogenesis of ischemia reperfusion (I/R) injury [12], and the reaction of NO with oxygen species results in the formation of toxic radicals, which are critical in the development of I/R injury and primary graft dysfunction (PGD) [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Increased arginase activity contributes to pathology after solid organ transplantation, and, in lung transplant recipients, arginase may contribute to organ dysfunction and impact on allograft perfusion, ventilation, acute rejection and graft remodeling [6].…”
mentioning
confidence: 99%